Ibn e Hummam and His book Fath ul Qadeer: Introduction and Methodology - Hussain, Mumtaz; AttaurRahman (Journal of Islamic and Religious Studies, 2017)
Fath ul Qadeer is one of the most comprehensive and well organized works in the Hanafi School of thought. Full name of this book is Fath ul Qadeer Lel ‘Aajez el Faqeer. It is a commentary and illustration of Hedaya, the most popular and authentic book in Islamic jurisprudence and in Islamic schools of thought. It is compendium of Islamic knowledge with a discussion on various subjects that are from various types of fiqh and Usool-e-fiqh. Author, Ibn e Hamam used a critical explanation of words from lexical to technical, their grammatical analysis, connection on the basis of grammatical and syntax regulations and illustration of differences between synonyms. The methodology of this book is unique as it provide unprejudiced and impartial in analysis of various topics under discussion and the rational and logical arguments given by the author in support of his view make this book a significant work and a remarkable milestone in fiqh collections. The paper concludes with a comprehensive analysis of the aspects dealt with in terms of methodology and its characteristics.